Chemical composition and insecticidal activity of Mentha rotundifolia and Chrysanthemum coronarium essential oils against the tomato leaf miner, Tuta absoluta - Krache Farial; Boualem Malika; Benourad Fouzia; Touzout Nabil; Mihoub Adil; Subhan Danish; Sulaiman Ali Alharbi; Mohammad Javed Ansari; Abdullah A. Alarfaj (Scientific Reports)
Abstract Tuta absoluta is one of the most destructive pests of tomatoes. Chemical insecticides used to control this leafminer harm all organisms, increasing the risk to public health and the environment. Developing natural alternatives, such as bioinsecticides formulated from essential plant oils, is a key strategy to address this problem. These volatile compounds, derived from the secondary metabolic pathways of plants, exhibit targeted activity against specific pest species. Their use is consistent with an environmentally responsible framework that reduces adverse impacts on ecosystems, protects non-target organisms, safeguards human health, and enhances the efficacy of integrated crop management systems. This study aims to determine the chemical composition of the essential oils (EOs) of from round leaf mint (Mentha rotundifolia) and crown chrysanthemum (Chrysanthemum coronarium) and to evaluate their toxicity to T. absoluta larvae in-vitro. The chemical composition of EOs obtained by steam distillation from the leaves of the plants was analyzed by gas chromatography coupled with mass spectrometry (GC-MS). Indeed, 77 volatile compounds representing 98.19% of the total oil of M. rotundifolia, including cyclobutane acetonitrile, 1-methyl-2-(1-methyl ethenyl)-, terpinene-4-ol, p-menthane, germacrene D, caryophyllene and myrcene, were the main compounds. However, farnesene, myrcene, eugenol, germacrene D, phytol, and pinene were significant components among 69 compounds representing 95.39% of the total oil of C. coronarium. Results showed that the EOs were toxic to the different larval stages. According to the Finney method, concentrations 2.88 and 1.07% are the LC50 of M. rotundifolia and C. coronarium oils, which induce 50% mortality of T. absoluta within 7 days of exposure. Statistical analysis of in-vitro tests showed that both EOs had a similar level of insecticidal efficacy by contact. The overall results showed that the oils used have been shown to have an important insecticidal effect and can be used as a source of biological and natural treatment against tomato leafminer (TLM).